Development of Self-Concept in Children's Home-Based Educational Processes in Preschool Educational Organization (The Peerian Journal, 2024)
This article presents some opinions on the development of the concept of "I" in the home-based education process of children in the preschool education organization. In addition, the article contains comments on the development of the mental and physical capabilities of the children of the preschool educational organization through the game.